How Long Is Safe? Setting the Cutoff for Uncomplicated Third Stage Length: A Retrospective Case–Control Study. Issue 1 (10th November 2015) - Shinar, Shiri; Schwartz, Anat; Maslovitz, Sharon; Many, Ariel
Abstract: Objective: The aim of our study was to determine the optimal time for manual placental removal in an uncomplicated third stage while taking into consideration the risk for blood transfusion. Risk factors for postpartum blood transfusions were studied. Methods: Computerized data of all vaginal deliveries at our labor and delivery unit from 2010 to 2014 were obtained. Cases of complete and spontaneous placental separation up to 60 minutes into the third stage of labor were extracted for analysis. Patient demographics, obstetrical history, delivery course, and outcome were assessed as well as blood product requirements during the postpartum period. Receiver–operating curves (ROC) for prediction of blood transfusion during the third stage were calculated and risk factors were assessed. Results: 31, 226 vaginal deliveries occurred during the study period and 28, 586 deliveries culminated with complete and spontaneous placental separation, 25, 160 of which met inclusion criteria. Independent risk factors for blood transfusions were primiparity, longer second and third stage length, labor induction, and maternal intrapartum fever. ROC curves showed that the optimal cutoff for the prediction of blood transfusions was 17 minutes into the third stage of labor. Waiting more than 30 minutes for placental separation increases the risk for blood transfusion more than threefold. Conclusions: A third stage longer than 17 minutes is associated with an increased risk for blood transfusion postpartum. After more than 30 minutes, the risk for blood transfusions increases more than threefold.